2016
DOI: 10.1158/1055-9965.epi-15-1126
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Residential Segregation and Neighborhood Characteristics on Surgery and Survival in Patients with Early-Stage Non–Small Cell Lung Cancer

Abstract: Background: Although the negative effects of lower socioeconomic status on non-small cell lung cancer (NSCLC) treatment and survival have been widely studied, the impact of residential segregation on prognosis and the receipt of treatment has yet to be determined.Methods: This is a retrospective, cohort study of NSCLC patients in Georgia (2000-2009; n ¼ 8,322) using data from the Georgia Comprehensive Cancer Registry. The effects of segregation, economic deprivation, and combined segregation/deprivation on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 52 publications
1
36
0
1
Order By: Relevance
“…While this finding may seem surprising, the relationship between residential segregation and Black cancer outcomes remains unclear. Some studies have found detrimental outcomes (as we did for urban locales) [22][23], while others have shown protective effects (as we did for rural locales) [18,26,38], and others have reported non-association [19,21,[39][40]. It is clear that the interaction of rurality and race, especially in segregated communities, deserves additional exploration in health research.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…While this finding may seem surprising, the relationship between residential segregation and Black cancer outcomes remains unclear. Some studies have found detrimental outcomes (as we did for urban locales) [22][23], while others have shown protective effects (as we did for rural locales) [18,26,38], and others have reported non-association [19,21,[39][40]. It is clear that the interaction of rurality and race, especially in segregated communities, deserves additional exploration in health research.…”
Section: Discussionsupporting
confidence: 49%
“…In highly-segregated areas, some studies report lower breast cancer and all-cause mortality for Black but not White women [18], higher breast cancer mortality for Black but not White women [19], and no associations between segregation and Black female breast cancer mortality [20][21] or survival [20]. For lung cancer, segregation has been linked to higher mortality rates for Black residents, but for White residents living in segregated areas, this association is either lower [22] or non-existent [23]. Given that the evidence on the effect of segregation on cancer outcomes is inconclusive, further investigation is needed to better understand these associations to assess allocation of resources and education for underserved and disparate populations in segregated areas.…”
Section: Introductionmentioning
confidence: 99%
“…12,50 Finally, in two lung cancer studies, higher segregation was associated with greater mortality among Blacks, but not Whites. 51,52 …”
Section: Resultsmentioning
confidence: 99%
“…52,56 Finally, in 2 lung cancer studies, higher segregation was associated with greater mortality among blacks, but not among whites. 44,53 Findings are less consistent across the 11 studies that examined Hispanic ethnic density. Three studies included measures of residential segregation; of these, 2 used the location quotient and identified a positive association between Hispanic segregation and greater breast cancerspecific or overall mortality.…”
Section: Survival or Mortalitymentioning
confidence: 91%
“…In this article (Cancer Epidemiol Biomarkers Prev 2016;25:750-8), which appeared in the May 2016 issue of Cancer Epidemiology, Biomarkers and Prevention (1), the authors regret that the variable "Age at Diagnosis" in Table 1 had been labeled incorrectly. "Age at Diagnosis" has changed from " 30-50; 51-64; 65-85" to "30-64; 65-74; 75-85.…”
mentioning
confidence: 99%